CONSTRUCTION OF NEGATIONS IN THE CONTEXT OF CRITICAL THINKING FOR PRIMARY SCHOOL - Sondore, Anita; Krastiņa, Elfrīda; Daugulis, Pēteris; Drelinga, Elga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the modern study process it is important to teach pupils critical thinking and involvement in decision making. Formulation of negations and construction of counterexamples is one of the ingredients of critical thinking which are stressed in the new project of the mathematical standard for primary school „Skola 2030” in Latvia. The goal of this study is to analyze experience and skills of primary school pupils and students of teacher study programs, which are related to the ability to formulate negations and counterexamples. A qualitative and quantitative analysis of questionaire answers given by pupils and future teachers is performed in this study. Results of this study show that pupils make mistakes constructing negations and counterexamples. Teachers also have problems constructing correct assertions. These observations should stimulate universities to pay attention to teacher preparation in this sense. Teachers should teach correct usage of the negation operation at different levels of difficulty and correct construction of counterexamples.